Implementation of Preterm Birth Interventions by Nurse Midwives during Provision of Intrapartum and Perinatal Care in Embu County, Kenya - Ndwiga, Edith Wamuyu; Keraka, Margaret; Kodhiambo, Maurice Onditi (Global Journal of Health Sciences, 2019)
Purpose: The purpose of the study was to investigate implementation of preterm birth interventions by Nurse Midwives during provision of intrapartum and perinatal care in Embu County, Kenya. Methodology: The study used descriptive cross-sectional design. 24 client's files (quarter of the sample size) were reviewed to ascertain implementation. 94 respondents were randomly sampled and self- administered questionnaires, document review guide and key informant guide were used to collect data. Data was analyzed by use of SPSS, descriptive statistics, chi squire and Fisher's exact test and binary logistic model. Findings were presented using tables and charts. Results: The study results revealed that there is a statistically significant association between, type of PTBI, survival rate of babies exposed to preterm birth interventions (PTBI) and proportion of nurse midwives implementing PTBI and the implementation of PTBI. However, the study concluded that implementation of PTBI is low at (52.7%) in Embu County, Kenya. Unique contribution to theory, practice and policy: In light of the research findings, the study recommends the county government of Embu and the hospital management to consider maternity waiting homes which can help bridge the gap between home and facility care especially for women who live far away from the healthcare facilities and presents with preterm birth interventions (PTB). Skilled care is also recommended to ensure an effective continuum of care from home to facility. The government is also recommended to invest in the training and induction of more nurses in the field of PTBI.